Analisis Penggunaan Model Pembelajaran Group Investigation (Investigasi Kelompok) Pada Mata Pelajaran Kearsipan di Smkn 1 Lamongan - Ririn Oktisa Widyaningsih; Durinta Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The changes in learning followed by the 2013 curriculum to the 2013 revised 2018 curriculum, learning is required to be student-centered so that students will become more active, think critically, and be able to communicate well. This study aims to describe the use of the Group Investigation learning model in Filing subjects in SMK 1 Lamongan. This type of research is a qualitative descriptive study. The research subjects were 3 students of class X OTKP and 2 students of class X OTKP as source triangulation. Data collection techniques used were interviews and questionnaires. Data analysis techniques in this study used data collection, data reduction, data presentation, and drawing conclusions. The results showed that: 1) the division of groups and sub topics carried out by students; 2) students choose to plan assignments in advance by dividing assignments to each group member; 3) students investigate the problem given by analyzing the answers of other group members; 4) students collect all the answers from members of the group and will present it according to the agreement that was made at the beginning of learning; 5) student presentations; 5) students understand learning when they ask and listen to the answers that have been delivered at the time of presentation and afterwards.